23Na chemical shift imaging in the living rat brain using a chemical shift agent, Tm(DOTP)5- - Bajwa, Awais Akbar; Neubauer, Andreas; Schwerter, Michael; Schilling, Lothar (Magnetic resonance materials in physics, biology and medicine, 2023)
It is well known that the use of shift reagents (SRs) in nuclear magnetic resonance (NMR) studies is substantially limited by an intact blood-brain barrier (BBB). The current study aims to develop a method enabling chemical shift imaging in the living rat brain under physiological conditions using an SR, Tm[DOTP]5−.